2016
DOI: 10.5527/wjn.v5.i5.471
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal level of vitamin D in non-dialysis chronic kidney disease population?

Abstract: AIMTo evaluate thresholds for serum 25(OH)D concentrations in relation to death, kidney progression and hospitalization in non-dialysis chronic kidney disease (CKD) population. METHODSFour hundred and seventy non-dialysis 3-5 stage CKD patients participating in OSERCE-2 study, a prospective, multicenter, cohort study, were prospectively evaluated and categorized into 3 groups according to 25(OH)D levels at enrollment (less than 20 ng/mL, between 20 and 29 ng/mL, and at or above 30 ng/mL), considering 25(OH)D b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…The pleiotropic effects of vitamin D fit well with the potential benefits of multifactorial nephrology care in CKD in non-dialysis as in dialysis setting [ 43 46 ]. To date, however, we have no solid data, that is, generated by well-designed controlled trials, demonstrating that the administration of native vitamin D in CKD patients ameliorates “hard” clinical outcomes besides and beyond the metabolic profile [ 47 51 ].…”
Section: Questions and Answersmentioning
confidence: 86%
“…The pleiotropic effects of vitamin D fit well with the potential benefits of multifactorial nephrology care in CKD in non-dialysis as in dialysis setting [ 43 46 ]. To date, however, we have no solid data, that is, generated by well-designed controlled trials, demonstrating that the administration of native vitamin D in CKD patients ameliorates “hard” clinical outcomes besides and beyond the metabolic profile [ 47 51 ].…”
Section: Questions and Answersmentioning
confidence: 86%
“…risk of death, kidney progression, and hospitalization, with the respective concentrations of 17.4 ng/mL (43.4 nmol/L), 18.6 ng/mL (46.4 nmol/L), and 19.0 ng/mL (47.4 nmol/L), denoting the highest risk prediction sensitivity and specificity 171. …”
mentioning
confidence: 99%
“…A prospective 3-year study of 470 unsupplemented non-dialysis patients in Spain with stage 3–5 CKD reported that those with baseline 25(OH)D values between 20 and 30 ng/mL had better survival, lower hospitalization, and better composite renal endpoints than those with lower or higher baseline concentrations [51], but found no additional benefits from raising serum 25(OH)D concentration to >30 ng/mL.…”
Section: Resultsmentioning
confidence: 99%